A hypothetical adhesin protein induces anti-biofilm antibodies against multi-drug resistant Acinetobacter baumannii. (October 2021) - de Freitas, Stella Buchhorn; Wozeak, Daniela Rodriguero; Neto, Amilton Seixas; Cardoso, Thayná Laner; Hartwig, Daiane Drawanz
Abstract: The increase in multidrug-resistant (MDR) Acinetobacter baumannii strains in hospital environments has generated great concern around the world. Biofilm is one of the forms of bacterial adaptation that is increasingly leading to antimicrobial resistance and therapeutic failure. The search for alternative therapeutic strategies, especially non-antibiotic-based, is urgently needed. In this study, we produce polyclonal antibodies (pAbs) in murine models against recombinant CAM87009.1 antigen, an A. baumannii fimbriae protein. The pAbs produced were isotyped and anti-biofilm activity evaluated in the A. baumannii ATCC® 19606 standard strain and nine MDR clinical isolates. All clinical isolates were analyzed for the presence of the cam87009.1 gene using the PCR technique, and one of the isolates did not have the gene in its genome. After four intraperitoneal immunizations (days 0, 14, 21, and 28) of mice with rCAM87009.1 and Freund's adjuvant, a significant antibody titer was detected by indirect enzyme-linked immunosorbent assay (ELISA) since the first immunization (1:6400), and the level increased until the 4th immunization (1:819, 200). IgM, IgA, IgG1, IgG2a, IgG2b, and IgG3 isotypes were identified in the serum of immunized mice ( P  < 0.001). The anti-rCAM87009.1 pAb was able to inhibit biofilm formation in 80 % of the strains evaluated in this study, including the ATCC® 19606 strain. The rCAM87009.1 proves to be a promising target in the development of alternative strategies to control biofilm-forming in A. baumannii MDR strains. Highlights: rCAM87009.1 protein is a target to develop strategies for control of infections caused by A. baumannii. pAb against rCAM87009.1 appear to be good alternatives to the use of antimicrobials. anti-rCAM87009.1 pAb are effective in the inhibit biofilm formation.